2016
DOI: 10.1037/cou0000112
|View full text |Cite
|
Sign up to set email alerts
|

As good as it gets? Therapy outcomes of trainees over time.

Abstract: There is a paucity of empirical studies that demonstrate psychotherapy trainees improve at assisting their clients' therapy outcomes over time. We examined whether trainees (i.e., practicum, predoctoral interns, and postdoctoral fellows) improved in their clients' therapy outcomes over time. We examined 114 trainees (i.e., who were trainees for the first client in the database) and had over 12 months of client outcome data (M = 45.31 months). At the start of their time in our database, about half of the partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 33 publications
1
45
0
2
Order By: Relevance
“…Of the 89 interviewees across the studies, 18% were male reflecting statistics reported about the gender balance in some fields of psychotherapy (for example, Robinson et al, 2017 ). This gender ratio also reflects the male-female make up of respondents in surveys of therapy trainees (for example, Owen et al, 2016 ). However, there is no way to find out the gender balance in therapy training courses for the review period.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Of the 89 interviewees across the studies, 18% were male reflecting statistics reported about the gender balance in some fields of psychotherapy (for example, Robinson et al, 2017 ). This gender ratio also reflects the male-female make up of respondents in surveys of therapy trainees (for example, Owen et al, 2016 ). However, there is no way to find out the gender balance in therapy training courses for the review period.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Hence, our results represent the effect of this treatment in the "practice phase." Although the SWs were given systematic and regular method-specific supervision, it is likely that their competence in providing IPC would have increased after a greater number of supervised, completed cases (Owen, Wampold, Kopta, Rousmaniere, & Miller, 2016). Although the IPC counselors adherence to clinical principles of IPC were relatively good, except for the use of communication analysis, role-playing, and decision analysis, further experience might have had a more positive effect on the results.…”
Section: Effectivenessmentioning
confidence: 99%
“…A large body of research concerns the influence of experience on therapist effectiveness, with the majority of studies finding no correlation between experience, therapy training, and treatment outcomes (Beutler et al, ; Erekson, Janis, Bailey, Cattani, & Pedersen, ). However, it has recently been found that therapists actually become less effective with experience (Goldberg, Rousmaniere et al, ), although some recent findings indicate that novice therapists actually improve with every year of experience, but with the improvement occurring mainly when treating clients whose symptoms are mild (Owen, Wampold, Kopta, Rousmaniere, & Miller, ). This finding is in line with the results of the present study, according to which therapist effectiveness is more relevant to clients with mild symptoms.…”
Section: Discussionmentioning
confidence: 99%